2022
DOI: 10.1155/2022/7987967
|View full text |Cite
|
Sign up to set email alerts
|

Construction, Validation, and Visualization of Two Web-Based Nomograms for Predicting Overall Survival and Cancer-Specific Survival in Elderly Patients with Primary Osseous Spinal Neoplasms

Abstract: Background. Primary osseous spinal neoplasms (POSNs) are the rarest tumor type in the spine. Very few studies have presented data on elderly patients with POSNs specifically. The present study was aimed at exploring the prognostic factors and developing two web-based nomograms to predict overall survival (OS) and cancer-specific survival (CSS) for this population. Method. The data of elderly patients with POSNs was extracted from the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…The nomogram is a user-friendly visual statistical model that incorporates multiple predictors and provides individualized survival prediction for clinicians and patients. It is extensively applied to a wide range of malignancies owing to its ease of use and reliable discriminative power (21)(22)(23). The nomogram for predicting survival in patients with CHS was established for the first time in the study of Song et al (11).…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram is a user-friendly visual statistical model that incorporates multiple predictors and provides individualized survival prediction for clinicians and patients. It is extensively applied to a wide range of malignancies owing to its ease of use and reliable discriminative power (21)(22)(23). The nomogram for predicting survival in patients with CHS was established for the first time in the study of Song et al (11).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, age, histological type, and surgery were determined to be independently associated with the OS rate of patients with POSNs with synchronous DM. Age at diagnosis was widely reported to be an important prognostic factor in primary malignant bone tumors ( 41 , 42 ). This study suggested that prognosis of patients with metastatic POSNs deteriorated gradually with age.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional staging systems, such as the AJCC TNM staging divide patients into four stages based on the all-or-nothing principle of classifying variables. They are, however, no longer the most effective way of categorising RLS patients into different prognosis groups 27 . Hence, a new predictive model is required.…”
Section: Discussionmentioning
confidence: 99%